A new species of grass fern, Schizaea erecta (Schizaeaceae), from Dinagat Island, Mindanao, Philippines - Amoroso, Victor B.; Acola, Mescel S.; Guiang, Maria Melanie M.; Acma, Florfe M.; Fritsch, Peter W.; Coritico, Fulgent P. (Phytotaxa, 2023)
Schizaea erecta Amoroso & Coritico (Schizaeaceae) from Dinagat Island, Mindanao, Philippines, is here described. This species is distinguished from other species of Schizaea by its consistently erect sterile and fertile fronds, narrow laminae, opposite sorophore lobes, rhizomes covered with short appressed brown scales, and oblong sporangia with apical annulus and conspicuous long, white hairs. A taxonomic key to the species of Philippine Schizaeaceae is provided.